Optimizing Cardiac Rehabilitation for Patients with Complex Coronary Disease without Revascularization - Afifuddin, Mokhammad; Tjahjono, Cholid Tri; Mayangsari, Veny (Universitas Brawijaya, 2025)
Patients with complex coronary artery disease (CAD) ineligible for revascularization present considerable management challenges and a high ischemic burden. Cardiac rehabilitation (CR), a comprehensive, multidisciplinary intervention, emerges as an essential non-pharmacological therapy. This review synthesizes the principles of CR, focusing on its profound pathophysiological benefits in this specific cohort. Mechanistically, CR confers pleiotropic effects: it enhances endothelial function via the eNOS/NO pathway, mitigates systemic inflammation through myokine regulation, promotes coronary collateralization (HIF-1α/VEGF pathway), and restores autonomic balance (HRV). Furthermore, CR integrates essential psychosocial support to address the high prevalence of depression and anxiety, which are independent risk factors. A primary objective, the improvement of quality of life (QoL), is consistently achieved through reduced anginal symptoms and enhanced functional status. Despite robust clinical and economic evidence demonstrating CR's efficacy in reducing MACE, mortality, and healthcare utilization, significant barriers to referral and adherence persist. Vigilant supervision and protocol adaptations are mandated for high-risk anatomical subsets, such as those with chronic total occlusions or severe left ventricular dysfunction